Harnessing delegation and technology to identify and manage malnutrition in a digital hospital: An implementation study. - Ellick, Jennifer; McCoy, Simone; Olufson, Hannah; Adams, Amanda; Banks, Merrilyn; Young, Adrienne (Nutrition & Dietetics, 2025)
Aims: Delegation of nutrition care activities to Dietetic Assistants in hospitals has been identified as one innovative malnutrition model of care, but there has been limited evaluation of their roles. This study aimed to develop, implement and evaluate a new Malnutrition Model of Care embracing automated delegation and digital systems. Methods: The Malnutrition Model of Care was created to detect patients at risk of malnutrition (using the Malnutrition Screening Tool) and nutritional decline (via routine intake tracking at all meals and snacks). Digital systems generated automated referrals to dietetics, with protocols to support Dietetic Assistants to action these to direct care escalation to the ward dietitian. Dietetic Assistant training included simulations and clinical task instructions. Implementation evaluation was guided by the Donabedian model of quality and included a review of inpatient dietetics occasions of service, survey of Dietetic Assistant role satisfaction and task confidence, and hospital‐wide cross‐sectional malnutrition audit. Data was descriptively analysed. Results: During the first year of implementation, 60% of Dietetics inpatient occasions of service were completed by Dietetic Assistants, with 26% of Dietetic Assistant inpatient tasks initiated from nursing malnutrition risk screening. Most Dietetic Assistants reported adequate training and confidence in completing delegated tasks. Malnutrition prevalence was 14% with no hospital‐acquired malnutrition identified. No clinical incidents were reported. Conclusions: The Dietetic Assistant workforce and technology were harnessed to implement an innovative delegated Malnutrition Model of Care that appears to be safe and effective at managing malnutrition from preliminary evaluation. Work continues to formally assess service efficiencies, cost and patient experience.